What is the role of ecological footprint on renewable energy deployment? Sustainability perspective for EU region - Bölük, Gülden; Demir, Fatih (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional Development, 2022)
Because of the concerns about global warming, climate change and energy security, issues many countries try to increase the share of renewable energy sources. Renewable energy has become key to ensure sustainable economic development as well. Therefore, the current study aims to analyze the role of environmental degradation, GDP, energy import and urbanization on renewable energy deployment in 26 European Union countries by using panel data over the 1990-2018 period. Against this backdrop, we employed Ecological Footprint to represent environmental degradation in these countries. Our results indicate that while GDP per capita and urbanization are not a significant driver of RE deployment, energy import and EFP negatively affect RE deployment. On the contrary, increasing GDP and urbanization have a deterring impact in some EU countries (Romania, Czechia, and Denmark). Moreover, energy requirement of growing income is mostly met by non-renewable energy and environmental pressure is not a strong driver for renewable energy development in the EU countries. We provided some policy recommendations in the conclusion part.